A Comparative Study of Impeller Modification Techniques on the Performance of the Pump as a Turbine - Abdulbasit Nasir; Edessa Dribssa; Misrak Girma; Tamerat Demeke (International Journal of Rotating Machinery)
The extensive use of the pump as a turbine (PAT) for micro-hydropower applications has a significant value from economic and technical viewpoints. However, the unavailability of the characteristics curve and relatively lower efficiency are the two basic limitations when considering pumps for power-generating applications. In this paper, the performance of the PAT is analyzed using the computational fluid dynamics (CFD) software called Ansys CFX in conjunction with standard k-ε. Then, experiments were done to verify the results of the simulation. Measurement inaccuracy effects are also taken into account. The initial performance of the PAT is refined by controlling basic design parameters (i.e., increasing the number of impeller blades, decreasing blade thickness, blade tip rounding, and adjusting blade inlet angle). Additionally, a new modification method known as blade grooving is also introduced in this research. Finally, all listed modification techniques are applied simultaneously to achieve maximum performance. The output of the study confirms that the adopted modification techniques have a positive effect on performance improvement. When the number of impellers is increased, the power output is enhanced by 5.72%, and blade grooving provides the most efficiency improvement, i.e., 7.00%. But decreasing blade thickness has no remarkable impact on the performance; the power output and efficiency are improved by 1.24% and 2.60%, respectively. The maximum performance improvement was achieved when the modification techniques are applied simultaneously with 10.56 and 10.20 percent of power and efficiency increments, respectively. From the entire study, it can be concluded that the chosen design parameters have an important effect on stabilizing the internal flow, decreasing the required head, decreasing the hydraulic loss in the impeller, and increasing the overall performance. The study also helps to figure out which modification technique is the most practical.